Spatial and Temporal Assessment of Nitrate-N under Rice-Wheat System in Riparian Wetlands of Punjab, North-Western India - Bhupinder S. Farmaha; Pritpal-Singh; Bijay-Singh (Agronomy, 2021)
The nitrate (NO3−) leaching assessment from extensive fertilizer nitrogen (N) applications to croplands is crucial to optimize fertilizer-N recommendations that do not threaten the quality of drinking groundwater. SWAP (Soil Water Atmosphere Plant), a water balance model, was linked with ANIMO (Agricultural NItrogen MOdel), a nitrate leaching model and the Geographical Information System (GIS) to assess the spatial and temporal leaching of NO3−-N from fields under rice-wheat cropping system in the riparian wetlands in the Punjab in north-western India. The results revealed that NO3−-N concentration in the groundwater exceeded the 10 mg NO3−-N L−1 limit set by the World Health Organization (WHO) for drinking water only during December–January. The verification of these results using measured values indicated that the SWAP-ANIMO model satisfactorily predicted NO3−-N concentrations in the leachate in the vadose zone. A low value of the mean absolute error (0.5–1.4) and a root mean square error (0.6–1.5) was observed between the measured and the predicted NO3−-N concentration across the soil profile during the validation at five sampling sites. The NO3−-N predictions revealed that in the long-term, the ongoing fertilizer-N management practices in the riparian wetlands will not significantly change the average NO3−-N concentration in the groundwater. The modeling approach was satisfactory for an efficient quantitative assessment of NO3−-N pollution in groundwater while accounting for the spatial and temporal variability.